The development of autopilot system for an unmanned aerial vehicle (UAV) helicopter model - Shamsudin, Syariful Syafiq (2007)
The aim of this research project is to develop an autopilot system that enables the helicopter model to carry out autonomous hover maneuver using on-board intelligence computer. The main goal of this project is to provide a comprehensive design methodology, implementation and testing of an autopilot system developed for a rotorcraft-based unmanned aerial vehicles (UAV). The autopilot system was designed to demonstrate autonomous maneuvers such as take-off and hovering flight capabilities. For the controller design, the nonlinear dynamic model of the Remote Control (RC) helicopter was built by employing Lumped Parameter approach comprising of four different subsystems such as actuator dynamics, rotary wing dynamics, force and moment generation process and rigid body dynamics. The nonlinear helicopter mathematical model was then linearized using small perturbation theory for stability analysis and linear feedback control system design. The linear state feedback for the stabilization of the helicopter was derived using Pole Placement method. The overall system consists of the helicopter with an on-board computer and a second computer serving as a ground station. While flight control is done on-board, mission planning and human user interaction take place on ground. Sensors used for autonomous operation include acceleration, magnetic field, and rotation sensors (Attitude and Heading Reference System) and ultrasonic transducers. The hardware, software and system architecture used to autonomously pilot the helicopter were described in detailed in this thesis. Series of test flights were conducted to verify autopilot system performance. The proposed hovering controller has shown capable of stabilizing the helicopter attitude angles. The work done for this project gives solid bases and chances for fast evolution of Universiti Teknologi Malaysia autonomous helicopter research.